2022
DOI: 10.3389/fped.2022.878924
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Potential of Gut Microbiota-Derived Short-Chain Fatty Acids in Preeclampsia

Abstract: Preeclampsia (PE) is a complex pregnancy-related hypertensive disorder leading to multiorgan dysfunction. It has high maternal, fetal, and neonatal morbidity and mortality rates. The study of gut microbiota and its metabolites in PE deserves further exploration. Thirty-eight pregnant women with PE and 29 healthy pregnant women in the third trimester of their pregnancy were recruited in this study. We used a targeted metabolomics approach to evaluate the short-chain fatty acids (SCFAs) in serum samples. The cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…In contrast to other SCFAs, this study identified a significant increase in isobutyric acid in the maternal serum of patients with ICP. Your previous research has also noted that the level of isobutyric acid in the peripheral blood circulation of pregnant women with pregnancy complications, such as pre-eclampsia and gestational diabetes, significantly increased compared with the NP group, aligning with the findings of this study[ 5 , 21 ]. This suggests that isobutyric acid plays a pivotal role in promoting the progression of pregnancy complications.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to other SCFAs, this study identified a significant increase in isobutyric acid in the maternal serum of patients with ICP. Your previous research has also noted that the level of isobutyric acid in the peripheral blood circulation of pregnant women with pregnancy complications, such as pre-eclampsia and gestational diabetes, significantly increased compared with the NP group, aligning with the findings of this study[ 5 , 21 ]. This suggests that isobutyric acid plays a pivotal role in promoting the progression of pregnancy complications.…”
Section: Discussionsupporting
confidence: 91%
“…Quantitative analysis showed that compared with NP women, the content of isobutyric acid in the pregnancy complications groups was significantly higher, and the levels of other SCFAs were also significantly different from those in the NP group. ROC curve analysis showed that the sensitivity and specificity of acetic, propionic, and isobutyric acids in the PE group were high (AUC > 0.9), which is consistent with a previous study ( Li et al., 2022 ). In addition, we also showed that SCFAs were closely related to the increased risk of ICP, and ROC curve analysis showed that caproic acid and isobutyric acid might be potential biomarkers (AUC > 0.9).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, Sivaprakasam et al reported that MCTs are involved in the uptake of short-chain fatty acids (SCFAs) through the plasma membrane [ 40 ]. Li et al found that several types of SCFAs were increased in patients with preeclampsia and are positively correlated with systolic, and diastolic blood pressure levels [ 41 ]. Our extracellular metabolite profiling pinpointed that the uptake of SCFA increased significantly when extracellular adenosine concentration increased ( Fig.…”
Section: Discussionmentioning
confidence: 99%